(untitled) (International Journal of Geoscience, Engineering and Technology, 2021)
Concrete is the most used material in civil construction due to its capacity, applicability and versatility. Thus, it is of fundamental importance to achieve the main properties of this element, which is durability and resistance. However, it is observed in practice the negligence in the concrete curing process. This work consists of a theoretical and experimental research on the influence of the curing method on the compressive strength of concrete. The concrete was dosed to obtain a characteristic compressive strength of 29.8 MPa, with the following curing methods: immersion curing, outdoor curing, wet chamber curing and spray curing twice a day. The performance of the specimens for each established curing method was analyzed, and the highest average strength obtained was obtained from the specimens cured by immersion, reaching an average compressive strength (fcm) of 35.40 MPa. The cured specimens cured in a humid chamber obtained an average resistance of 33, 82 MPa, followed by spray curing twice a day, with an average resistance of 32.87 MPa, and finally the cure in the open air, with an average of 30.95 MPa. In addition, the research shows that the procedure suggested by the norm for molding the specimens is inefficient in terms of maintaining a good compactness of the concrete mass, which caused the specimens, in general, sets of voids, causing high levels of standard deviations.